Vocabulary Enhancement Through Role Play Technique - Katemba, Caroline V. (8ISC Abstract Proceedings, 2022)
Vocabulary is a core in language learning. Young learners need to master their vocabulary in order to understand the foreign language. Therefore the purpose of this study was to identify the effectiveness of the Role-Play technique in improving students’ Vocabulary enhancement. Specifically, it intended to answer: Is there any significant difference between the students who were taught through Role Play and those who were not taught through Role Play. This study was quantitative research, and the design was experimental. 68 grade VIII students of SMPN 3 Cisarua participated in this study. They were divided into two groups, VIII B as the control group and VIII A as the experimental group. These two groups took the same pre-test. The experimental group used Role-Play technique, and the control group used the conventional method. At the end of the treatment, both groups took the same post-test. Based on the analysis, there was a significant difference in students’ vocabulary enhancement between those who were taught through the Role Play technique and those who were taught through the conventional method. From this research, the researcher concludes that the use of Role Play can enhance a student's vocabulary. Keywords : Role-Play, Vocabulary improvement, Vocabulary Acquisition